Sticky Affections: María Zambrano's "La Cuba secreta" and Transatlantic Relationality. - Russell, Ian (Hispanic Review)
"La Cuba Secreta" (1948) has been a germinal text for the study of exiled Spanish writer María Zambrano's work on national, poetic, and subjective identity formation. In this essay, I focus specifically on the apego (attachment) she feels for Cuba in order to explore how affective relations, for Zambrano, could potentially avoid the violent hierarchies imposed by Enlightenment values. I analyze the sites where apego signals an intersubjective immersion as a mode of radically anti-Enlightenment relationality. However, while the sticky relation between Zambrano and the island might avoid Rationalism's destructive subject–object boundaries, it is also tethered to the destruction of subjectivity occasioned by the island's racial and colonial traumas. Ultimately, I suggest that Zambrano's apego is a compelling example of relations for the field of Transatlantic Studies that wishes to avoid the hierarchies of modernity while still bringing to the surface the traumas and violence of racism and colonialism.